Near fatal intoxication by nicotine and propylene glycol injection: a case report of an e-liquid poisoning - Mhedi Belkoniene; Jennifer Socquet; Denise Njemba-Freiburghaus; Cyril Pellaton (BMC, 2019)
Abstract Background Concern about intoxication by e-liquid is growing as calls to poison control centers have increased since their introduction. Only three cases of intoxication by injection have been reported worldwide. Our case is unique because of the precise follow-up of a patient who survived a lethal dose of self-injected e-liquid, without other co-intoxication. Case presentation A 51-year-old male presented to the Emergency Department after injecting himself intravenously (IV) in the forearm with 10 mL of e-liquid (1000 mg of nicotine diluted in propylene glycol). An agitation phase was followed by coma and bradypnoea requiring mechanical ventilation. The patient developed a transitory neurological impairment with the appearance of tetraparesis, gaze palsy and myoclonus due to nicotinic syndrome. The arterial blood gas (ABG) analysis confirmed uncompensated lactic acidosis with an elevated anion gap, which is an expected effect of propylene glycol. The toxicology screen indicated the presence of nicotine and cotinine in the blood and excluded the presence of concomitant intoxication. The patient recovered without sequelae. Conclusion Even a small quantity of intravenous (IV) e-liquid can lead to an acute intoxication and fatal outcomes due to the toxic effects of nicotine. This case might help emergency doctors cope with acute intoxication by injection of e-liquid and increase their comprehension of the two main substances, nicotine and propylene glycol with overview of their pharmacodynamics and kinetic effects.